Questionnaire study of application about sentinel lymph node biopsy surgery in locally advanced breast cancer patients who received neoadjuvant chemotherapy - Lee, Eun-Gyeong; Lee, Minjung; Jung, So-Youn; Han, Jai Hong; Kim, Seok-Ki; Lee, Seeyoun (Frontiers in Oncology, 2023)
Background Nodal staging from sentinel lymph node (SLN) biopsy has become the standard procedure for early-stage breast cancer patients. SLN biopsy implementation after chemotherapy has previously been evaluated. This questionnaire study aimed to investigate the current trend of SLN biopsy after neoadjuvant chemotherapy (NAC) for locally advanced breast cancer. Methods and materials We conducted a web-based survey among breast surgeons who are members of the Korean Breast Cancer Society. The survey comprised 14 questions about axillary surgery after NAC. Results Of 135 respondents, 48.1% used a combined method of dye and radioactive isotope (RI). In the absence of SLN metastasis, 67.7% would perform only SLN biopsy, while 3% would perform ALN dissection. In case of SLN metastasis, the proportions of surgeons who would proceed with ALN dissection were 60.2% and 67.2% for less than two and more than three positive SLNs, respectively. Conclusion The present study confirmed the increasing tendency to adopt SLN biopsy for axillary staging in patients who achieved complete response with initial nodal metastasis. It could be expected that the mapping methods for patients receiving NAC have become diverse, including RI, vital dye, and indocyanine green fluorescence. The implementation of SLN biopsy after NAC will grow in the coming years due to an increasing demand of minimally invasive surgery.